Modified hybrid L-Z source inverter - A closed loop perspective - Chauhan A.K.; Jain M.; Singh S.K. (My University, 2025)
Dual output converter are proposed in different literature. These converters has potential to supply AC and DC load simultaneously. But standalone operation and DCM phenomenon presence is the problem of converter in initial proposals. However, both these problems are counteract by introduction of antiparallel switch in Modified hybrid L-ZSI(MHLZSI). With this modification, the control technique is changed and has to supply one more PWM pulse. In open loop control, it is easy to provide the control pulse and Moreover it does not regulate the output. This paper proposes the closed loop study of MHLZSI. State-space analysis is done with reference to both DC load and AC load to reach out at the final transfer function in terms of control to output. DC and AC voltage control is designed using PI control. Both the controller includes the current control and voltage control loop. The inclusion of current loop in the system, makes transient to damped out quickly. The controllers are evaluated based on 1) the DC and AC reference voltage tracking 2) DC and AC load disturbance rejection. The simulation analysis is presented to provide the conclusive results. © IEEE.